2019
DOI: 10.3389/fpsyg.2019.02332
|View full text |Cite
|
Sign up to set email alerts
|

Schoolchildren’s Compensatory Strategies and Skills in Relation to Attention and Executive Function App Training

Abstract: BackgroundGiven the importance of attention and executive functions (EF) in children’s behavior, programs aimed at improving these processes are of special interest. Nexxo-training combines the use of the Nexxo touchscreen application (inhibition and vigilance tasks) with procedural metacognitive strategies (imparted by an instructor) for all the individuals using the app, regardless of their level of ability, plus compensatory strategies based on individual child performance. This study presents an analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Our results suggest that, for some youth, particularly those high in frustration and low in executive control, additional or alternative emotion regulation strategies might be needed to support effective coping. Interventions might incorporate compensatory strategies or training to enhance inhibitory control (e.g., Rossignoli-Palomeque et al, 2019 ) or mindfulness practices (e.g., Long et al, 2021 ) to complement cognitive-behavioral coping strategies. Consideration of individual temperament differences in the delivery of coping enhancement or clinical intervention can support better emotion regulation and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that, for some youth, particularly those high in frustration and low in executive control, additional or alternative emotion regulation strategies might be needed to support effective coping. Interventions might incorporate compensatory strategies or training to enhance inhibitory control (e.g., Rossignoli-Palomeque et al, 2019 ) or mindfulness practices (e.g., Long et al, 2021 ) to complement cognitive-behavioral coping strategies. Consideration of individual temperament differences in the delivery of coping enhancement or clinical intervention can support better emotion regulation and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…However, the participants can generate them at will. Children from 4th grade onward can use strategies, but younger children cannot develop them independently (Pérez and Capilla, 2008;Rossignoli-Palomeque et al, 2020), although we can train them (Rossignoli-Palomeque et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] compiled studies that evaluated interventions to stimulate executive functions based on computer systems. Among these interventions aimed at children, serious games can be distinguished [ [31] , [32] ], some commercial video games [ [33] , [34] ], programs based on classic tasks [ [35] , [36] ]; interventions that incorporated virtual reality technology [ 37 ], among others. The authors also found that research on computational thinking training is another area of study that has shown different effects of teaching coding and programming on children's executive functions [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] ].…”
Section: Introductionmentioning
confidence: 99%